Reinvestigation of spermiogenesis in the proteocephalidean cestode Proteocephalus longicollis (Zeder, 1800) - Brunanská, Magdaléna; Scholz, Tomás; Nebesárová, Jana (The Journal of parasitology, 2004)
The reinvestigation of spermiogenesis in the proteocephalidean cestode Proteocephalus longicollis (Zeder, 1800) provides new details that were not described previously for this species. The 2 centrioles with roots are oriented at the first tangential to the long axis of the nucleus in a differentiation zone. They come to be arranged in the same plane only when a single intercentriolar body (ICB) appears between them. The ICB had been described previously as consisting of a number of dense elements (Swiderski, 1985) but, in the present study, appeared as a single, electron-dense plate. Also new for this species is the observation of 2 arching membranes that appear at the base of the differentiation zone only when the 2 flagella rotate toward the median cytoplasmic protrusion. Moreover, the formation of a crested body is described for the first time in P. longicollis. The present data support the suggestion that the process of spermiogenesis in proteocephalidean tapeworms corresponds in most features to that observed in some members of the unrelated tetraphyllidean clades, the Onchobothriidae and Phyllobothriidae. This may represent more evidence regarding the close relationship between tetraphyllidean and proteocephalidean cestodes, but existing information is fragmentary and controversial in some characters.
Keywords: Oncorhynchus mykiss; spermatogeneze; centrioly; zvířata; Cestoda; Testis; Spermatogenesis; flagella; mužské pohlaví; Centrioles; Flagella; Animals; testis; Microscopy, Electron; Male; elektronová mikroskopie